PSYCHOANALYSIS AND LACAN: A WALK THROUGH THE UNCONSCIOUS AND LANGUAGE - Chagas Ramos, Rawy (Health and Society, 2025)
This article offers a comprehensive analysis of Jacques Lacan’s psychoanalytic theory, emphasizing his critical reinterpretation of Freud and the central role of language in subject formation. Beginning with biographical and theoretical context, the author explores core concepts such as the Mirror Stage, the Imaginary, Symbolic, and Real registers, the Oedipus Complex, and the Name-of-the-Father. The paper also discusses the ethics of desire, the notion of the sinthome, and the subversion of the subject in contemporary society. It intertwines psychoanalysis, philosophy, linguistics, and clinical practice, highlighting the ongoing relevance of Lacan’s work in understanding psychic suffering and modern subjectivity. According to the author, Lacanian psychoanalysis provides a unique listening framework that resists normative standardization and upholds the singularity of human desire.